التربية الشخصية في تعليم اللغة العربية في المدرسة الثانوية الحكومية الخامسة غونونج كيدول - alfina; Muhammad Zaenuri; محمد زينوري ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2023)
Seeing the news circulating there are still many moral crises that occur in Schools. One solution is to apply character education in learning. Then the purpose of this study is to find out how the process of learning Arabic in The State Islamic Junior High School Five GunungKidul. This type of research is qualitative research with descriptive method. The source of the data from this study is the subject of valid and relevant data with data collection techniques in the form of interviews with Arabic teacher, principal, and student, then observe by direct observation. Data analysis conducted by researchers include four step namely data collection, data reduction, data exposure, and conclusions. The results of this study the teacher’s strategy in instilling character education in the learning process is divided into three activities namely preliminary activities, core activities, and finally closing activities. While the forms of character values in learning Arabic are religious, disciplined, honest, responsible,critical thinking and cooperation, curiosity, never give up, conscientious, careful, confident, healthy lifestyle, polite, love of knowledge, and creative.